Tipificação dos agricultores familiares no pólo citrícola do estado de Sergipe - Silva, Marito Bento da (2008)
The use of typology and indicators in the sustainable agriculture have allowed to reach confident and very important results for the agricultural activities. The objective of this work was to identify the types of the agriculturist that exist in the Pólo Citrícola of Sergipe state. For this, the use of the measure of similarity followed by the analysis of cluster, for the method of Ward's. Finally it was made a selection of sustainable indicators using the methodology of the Organization for the Cooperation and Economic Development - OCDE, the model of indicators Pressão-Estado-Impacto-Efeito-Resposta (PEI/ER). Seven types of agriculturist has been found and, about thirty sustainable indicators were chosen. We hope that the results reached in this research allowed to have a better perception of the family agriculturist situation in the Pólo Citrícola, as well as contributing in the adoption of sustainable public politicies for the region.